Revitalization of an amateur sports field with emerald grass - dos Santos, Patrick Luan Ferreira [UNESP]; do Nascimento, Matheus Vinícios Leal [UNESP]; Costa, João Victor [UNESP]; Bôas, Roberto Lyra Villas [UNESP] (FapUNIFESP (SciELO), 2020)
With the increasing popularization of football (soccer), new technologies have arrived in Brazil that assist in the maintenance of sports fields, making it possible to increase the quality of turfgrass in both professional and amateur fields. Thus, the revitalization process has become fundamental in sports fields installed with emerald grass to improve game performance and turfgrass development. The objective of this study was to revitalize an amateur sports field in the interior of São Paulo state, Brazil, planted with emerald grass. The conditions of the field were initially assessed and a set of revitalization procedures were carried out from No-vember 2019 to March 2020 to improve turfgrass quality, including: chemical analysis of the soil and liming; mowing of the grass and disposal of clippings; soil decompaction through aeration with solid tines; application of sand (top dressing); pest and weed control; planting of new sod; fertilization and maintenance. Technical training with employees was also conducted for subsequent field maintenance. All tested operations were essential and necessary to improve the aesthetics and quality of the amateur sports field, so that the turfgrass could be revitalized and ready for use in soccer matches.
Keywords: sports field; topdressing; turfgrass; Zoysia japonica